2013
DOI: 10.3109/09513590.2013.856409
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin-19 as a biomarker in urine and in serum for the diagnosis of endometriosis – a prospective study

Abstract: Endometriosis compromises the quality of life of countless women worldwide and is a leading cause of disability. Clinical symptoms of endometriosis can be very heterogeneous leading to a long interval between onset of symptoms and surgical diagnosis. A noninvasive, rapid diagnostic test is urgently needed. In this prospective study, we evaluated the usefulness of Cytokeratin-19 (CK19) as a biomarker for the diagnosis of endometriosis through urine and serum ELISA. 76 reproductive-aged women undergoing laparosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Thus, CK19 seems not to be a valuable urinary biomarker of PE, which might be attributed to the lack of understanding of the pathophysiology of excretion of cytokeratins in urine. This is also outlined by the fact that promising data indicating CK 19 as a valuable urinary biomarker for endometriosis could recently not be verified in a larger patient population by our group [22]. It could well be that CK 19 fragment is not primarily eliminated by renal clearance and thus is not suitable as a urinary biomarker at all.…”
Section: Commentmentioning
confidence: 87%
“…Thus, CK19 seems not to be a valuable urinary biomarker of PE, which might be attributed to the lack of understanding of the pathophysiology of excretion of cytokeratins in urine. This is also outlined by the fact that promising data indicating CK 19 as a valuable urinary biomarker for endometriosis could recently not be verified in a larger patient population by our group [22]. It could well be that CK 19 fragment is not primarily eliminated by renal clearance and thus is not suitable as a urinary biomarker at all.…”
Section: Commentmentioning
confidence: 87%
“…Cytokeratin-19 (CK19) is another molecule that could be used in the detection of endometriosis. Kuessel et al [141] measured urinary levels of CK19 by ELISA on a cohort of 76 women. The study concluded that there was no significant correlation between urinary levels of CK19 and endometriosis.…”
Section: Urinary Biomarkers In Endometriosismentioning
confidence: 99%
“…Using an immunoblot technique, Tokushige et al demonstrated cytokeratin-19 (CK19) to be uniquely expressed in 11 urine samples from women with histologically proven endometriosis relative to samples from 6 women free of disease [ 102 ]. A larger prospective study was subsequently unable to confirm the diagnostic potential for urinary CK19 [ 103 ], possibly due to different specimen collection techniques or different subject characteristics. As in serum, matrix metalloproteinases (MMPs) have been investigated for association with endometriosis.…”
Section: Urine Biomarkersmentioning
confidence: 99%